1998
DOI: 10.1103/physrevc.57.1210
|View full text |Cite
|
Sign up to set email alerts
|

Pion excess, nuclear correlations, and the interpretation of(p,n)spin transfer experiments

Abstract: Conventional theories of nuclear interactions predict a net increase in the distribution of virtual pions in nuclei relative to free nucleons. Analysis of data from several nuclear experiments has led to claims of evidence against such a pion excess. These conclusions are usually based on a collective theory (RPA) of the pions, which may be inadequate. The issue is the energy dependence of the nuclear response, which differs for theories with strong NN correlations from the RPA predictions. In the present pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The nucleon number k = 0 denotes the incident or exit nucleon. Then the polarization, the analyzing power and the polarization transfer coefficients are given respectively by 12) where i, j = x, y, z or q, n, p. The DWIA calculation is usually carried out in the [x,ŷ,ẑ] frame, while the [q,n,p] frame is sometimes more convenient for the theoretical analysis. The relation between D ij (i, j = q, n, p) and D ij (i, j = x, y, z) is given by 13) where θ p is the angle betweenp andẑ.…”
Section: General Formulas For Cross Section and Spin Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleon number k = 0 denotes the incident or exit nucleon. Then the polarization, the analyzing power and the polarization transfer coefficients are given respectively by 12) where i, j = x, y, z or q, n, p. The DWIA calculation is usually carried out in the [x,ŷ,ẑ] frame, while the [q,n,p] frame is sometimes more convenient for the theoretical analysis. The relation between D ij (i, j = q, n, p) and D ij (i, j = x, y, z) is given by 13) where θ p is the angle betweenp andẑ.…”
Section: General Formulas For Cross Section and Spin Observablesmentioning
confidence: 99%
“…From these results, it was concluded [10,11] that there is no enhancement of R L , namely no collective enhancement of the pionic modes, which was interpreted as evidence against the pion excess in the nucleus. With help of sum rules, Koltun [12] analyzed the data by means of a correlated nuclear theory, in which the two-nucleon correlation is dominating, and concluded that there is no disagreement between the data and the model for R L , but R T is not explained. He claimed that there is no collective enhancement of the pionic modes.…”
Section: Introductionmentioning
confidence: 99%
“…[243,244,245,246]. These studies include calculations within the delta-hole model [245], the role of NN correlations and the energy dependence of nuclear response functions [246], possible effects of "Brown-Rho scaling" on nuclear structure functions [243], and implications of low-energy pion-nucleus scattering data for nuclear deep-inelastic scattering and Drell-Yan production [244].…”
Section: Further Notesmentioning
confidence: 99%
“…The nucleon light-cone distribution functions are driven by the nuclear spectral function, which defines the energy-momentum distribution of bound nucleons [15][16][17][18][19][20][21][22]. The calculation of mesonic correction is less certain and model-dependent [34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%